2020
DOI: 10.1177/2325958219898457
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Stewardship: A Review of Published Outcomes with Recommendations for Program Implementation

Abstract: Persons living with HIV (PLWHs) are at high risk for medication errors when hospitalized, but antiretroviral medications are not often evaluated by antimicrobial stewardship programs (ASPs) because they are not specifically discussed in the standards of practice. However, antiretroviral (ARV) stewardship programs (ARVSPs) have been shown to decrease medication error rates and improve other outcomes. The goal of this article is to review published literature on ARVSPs and provide guidance on key aspects of ARVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…( 11 ) An analysis of 6 studies found a significant reduction in errors in the postimplementation of antiretroviral stewardship. ( 12 ) Furthermore, a stewardship protocol may optimize antifungal prescriptions. ( 13 )…”
Section: Discussionmentioning
confidence: 99%
“…( 11 ) An analysis of 6 studies found a significant reduction in errors in the postimplementation of antiretroviral stewardship. ( 12 ) Furthermore, a stewardship protocol may optimize antifungal prescriptions. ( 13 )…”
Section: Discussionmentioning
confidence: 99%
“…Despite the diverse etiologies of ICU admissions among PWH, guidance on pharmacotherapy-related decision-making tools specifically tailored to this critically ill patient population are lacking. A recent article emphasized the need for ART stewardship and provided recommendations for program consideration and implementation, highlighting the gap in literature compared to other commonly used medications for infectious diseases [ 94 ]. The proposed core elements for antiretroviral stewardship programs (ARVSPs) emphasized leadership commitment, accountability, drug expertise, key support, tracking, reporting, and comprehensive education.…”
Section: Antiretroviral Stewardship In the Icumentioning
confidence: 99%
“…In addition to clinical considerations, various programmatic elements are needed to help ensure success of the ASP. Taken from literature describing CMV AVS as well as HIV antiretroviral stewardship programs [27 ▪ ,30], the following core elements should be included in CMV ASP:…”
Section: Core Elements Of Cytomegalovirus Antiviral Stewardshipmentioning
confidence: 99%